Case Report: Effect of Conditioned Medium Nasal Drop (CMND) and Intravenous Umbilical Cord-Mesenchymal Stem Cells (UC-MSCsIV) on the function of cardio respiration after 4 years Percutaneous Coronary Intervention (PCI) in RSPAD Gatot Soebroto - Prayitno, G.D.; Pratama, V.; Pujowaskito, P.; Sartika, C.R.; Rahmawati, V.; Karina, N.; Faqih, A.M.; Haifa, R.; Dirgantara, Y.; Jundan, S.F.; Pratiwi, E.D.; Facicilia, G.; et al. (Cytotherapy (Oxford, England), 2020)
Coronary artery disease (CAD) is one of the leading cause of death in the world. Currently, the common therapy for this disease is to use drugs and surgical procedures however the result has been less optimum. Therefore, it is necessary to develop an alternative treatment using Mesenchymal Stem Cell (MSC) and Conditioned Medium (CM). MSCs were obtained from the umbilical cord of eligible donor and process in a cGMP-standardized laboratory certified by the Indonesian Ministry of Health. A 52-year-old subject who experienced Coronary Artery Disease was treated with PCI four years before the stem cell therapy. The subject signed an informed consent for stem cell therapy before the injection. Allogeneic UC-MSC for CAD was packed in a syringe containing 20 ml NaCl 0.9% with cell concentration of 20 × 106. Umbilical Cord-Mesenchymal Stem Cells were administered intravenously and conducted three times over 4 months period. Meanwhile, Conditioned Medium (CM) was applied intranasally with a dose of 0.4 cc/day for a week after each UC-MSCs administrated. Assessment with Magnetic Resonance Imaging (MRI) shows improvement on the Left Ventricular Ejection Fraction (LVEF) from 55% at baseline and 75% at 3 weeks after first stem cell transplantation. Endothelial Cell Progenitor (EPC) count show decreasing the number of EPC cells from 11,893 cells/mL into 4,932 cells/mL. This shows the angiogenesis process takes place after the UC-MSC injection. On the twelve weeks after the first injection, the subject undergo spirometry test and shows improvement in the vital capacity (85% into 94%), forced capacity (85% into 94%), and forced expansion volume (93% into 103%). There are no adverse events occur and the patient experience improvement in physic, MRI, laboratory and spirometry assessment.